Coffin–Siris Syndrome and the BAF Complex: Genotype–Phenotype Study in 63 Patients. Issue 11 (30th August 2013) - Santen, Gijs W.E.; Aten, Emmelien; Vulto‐van Silfhout, Anneke T.; Pottinger, Caroline; van, Bregje W.M.; van, Ivonne J.H.M.; Snowdowne, Ronelle; van der, Christian A.C.; Boogaard, Merel; Linssen, Margot M.L.; Vijfhuizen, Linda; van der, Michiel J.R.; et al.
<x xml:space="preserve">Abstract</x> This paper describes 63 patients diagnosed with Coffin‐Siris syndrome, identifying a pathogenic variant in 45. We present a genotype‐phenotype correlation and provide some recommendations for the clinical care of CSS patients. We show using EVS data that especially for SMARCA2, SMARCA4 and SMARCE1 it is difficult to discriminate between non‐pathogenic and pathogenic variants without access to parental DNA, and we recommend analysing parental samples. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>